Analytical and Experimental Calculation of a Three-phase Induction Motor Using Maxwell - حسن عزت; بدر زيد; زيتي همام (Latakia University Journal -Engineering Sciences Series, 2021)
Due to the important information provided by the induction motor characteristics as its performance and efficiency, as it allows the calculation of all values ​​that determine the motor’s operating system at different loads. In this paper, we will present an analysis the three-phase induction motor characteristics Using one of the most popular programs currently designed to simulate electrical machines, the Maxwell program, and compare the simulation results with experimental tests. The experiments were conducted in the electrical machines laboratory at Tishreen University by. Comparing the results obtained with the simulation results, it was found that the experimental results are close to the simulation results, and sometimes identical to it. except for the presence of some anomalies.